Experimental Analysis of â€œBA-TPFâ€ Technique for Regression Test Optimization - Dalal, Sandeep; r, Sudhi; Solanki, Kamna (International Journal of Engineering & Technology, 2018)
Regression testing focuses on finding those newer faults that may get introduced in the software during the process of fixing the older faults. Therefore, it becomes mandatory to re-test the software system after modifications and amendments to detect these undesired faults. The most important observation in this regard is to understand the fact that it becomes impractical for the software testing team to run the entire set of test cases again during regression testing phase due to cost, time and resource constraints. The ultimate way to deal this complexity of regression testing is to run the optimized set of test cases that can serve the purpose of regression testing without compromising the quality of the test suite. A novel technique â€œBA-TPFâ€ has been proposed recently in this regard for test suite optimization in regression testing. This paper describes the experimental evaluation of the proposed technique and performance of the proposed technique has been evaluated using TCP, PRT and APPC metrices.